9.8 BRIDGING THE DIVIDE: HOW LINGUISTIC BRANCHES INTERTWINE WITH TYPOLOGY - Yoqubjonova Iqbola (Innovative technologies in construction Scientific Journal, 2024)
Ushbu maqola tilshunoslikning turli sohalari va tipologiya o’rtasidagi bog’liqlikni o’rganib, bu qiyosiy yondashuv til xilma-xilligi va universalligini tushunishimizni qanday boyitishiga urg’u beradi. Tayanch so’zlar: Tilshunoslik, tipologiya, til universallari, tillararo taqqoslash, til tuzilishi, fonetika, fonologiya, morfologiya, sintaksis, semantika, tarixiy tilshunoslik, psixolingvistika, sotsiolingvistika Аннотатсия: В данной статье исследуется взаимосвязь между различными областями лингвистики и типологией, подчеркивая, как сравнительный подход обогащает наше понимание языкового разнообразия и универсалий. Ключевые слова: лингвистика, типология, языковые универсалии, межъязыковое сравнение, структура языка, фонетика, фонология, морфология, синтаксис, семантика, историческая лингвистика, психолингвистика, социолингвистика Annotation: This article explores the interconnectedness between various branches of linguistics and the field of typology, highlighting how this comparative approach enhances our understanding of language diversity and universality. Keywords: Linguistics, typology, language universals, cross-linguistic comparison, language structure, phonetics, phonology, morphology, syntax, semantics, historical linguistics, psycholinguistics, sociolinguistics Introduction. Linguistics, the scientific study of language, encompasses numerous branches, each focusing on a specific aspect of this complex human phenomenon. From the intricacies of sound systems to the evolution of languages, each branch offers a unique perspective. However, a common thread unites them: typology, the systematic classification of languages based on shared structural features. As Croft (2003) aptly states, "Typology is the study of systematic cross-linguistic variation," seeking to uncover patterns and tendencies that transcend individual language families. Methods. This article employs a literature review approach, drawing upon research from various linguistic branches to demonstrate how typology informs and enriches their respective inquiries. Examples from diverse languages illustrate the interplay between specific linguistic features and typological classifications. The World Atlas of Language Structures (WALS), an extensive online database documenting structural features of over 2,000 languages (Dryer & Haspelmath, 2013), serves as a valuable resource for this comparative analysis. Results The analysis reveals a strong connection between linguistic branches and typology: Phonetics and Phonology: Typology identifies recurring sound patterns across languages, such as the widespread preference for symmetrical vowel inventories (Ladefoged & Maddieson, 1996). For example, typological studies have shown that languages with five vowels typically organize them in a triangular pattern, with /i/, /u/, and /a/ forming the corners (Maddieson, 1984).